Entre florestas e humanos: um olhar sobre os ungulados do Espírito Santo - Seibert, Jardel Brandão (2021)
Large ungulates represent an important group in the Neotropical region and are feared, over time, with anthropogenic pressures, mainly with hunting and habitat loss and fragmentation. The occurrence and distribution of species in the landscape are influenced by the existence of favorable conditions and by the availability of resources that specific species, and sometimes wild animals, frequent agricultural areas close to forest regions. In the present study, it was evaluated how biotic and abiotic variables interfere in the occupation pattern of ungulates, in addition to understanding how ecological and anthropogenic factors influence the interaction between ungulates and the local human community in one of the last remnants of the Tabuleiro’s Atlantic Forest. The study was carried out in the Linhares-Sooretama Forest Complex (CFLS), located in the north of Espírito Santo state, southeastern Brazil. To estimate the occupation of ungulates in the study area, we used the single-species, singleseason occupation model. To understand how the interaction between ungulates and the local human community takes place, they were chosen in the areas of direct and indirect influence of the study area, in two sampling campaigns, between January and April of 2018 and 2019. With the models, it was possible to differentiate the areas of use of the species, even at low incidence rates, and both anthropogenic and biological variables influence the occupation of ungulates in the study area, being found from anthropized areas, a wide range of plant formations and different degrees of fragmentation. Associated with the proximity between agricultural areas and large blocks of forest, the tapir was the most common species seen on rural properties, followed by deer and the peccaries. And it was observed that the smaller the distance between the rural property and the Biological Reserve of Sooretama and an area cultivated on the properties, the greater the possibility of interaction between the ungulates and the local human community, however, no damage was reported to the interviewees and no injuries to the ungulates. Thus, we emphasize that the CFLS has a variety of environments that are occupied in a particular way by each species of ungulates, and even species that tolerate areas with a pronounced level of anthropization (tapirs and collared peccaries), are closely associated with the forest environment, and confirm that species occurring in areas with an intermediate level of anthropization (Deer), in addition to using forest areas, demonstrate tolerance to more disturbed places. In this way, the coexistence between humans and wild animals is possible through a mitigation strategy and the present study is important for the delimitation of effective actions. Therefore, we understand that ungulates have a certain environmental plasticity in the CFLS, but we emphasize the need to maintain intact forest blocks for the species to persist in the region.